Climate change and prolongation of growing season: changes in regional potential for field crop production in Finland - P. PELTONEN-SAINIO; L. JAUHIAINEN; K. HAKALA (Agricultural and Food Science, 2008)
Climate change offers new opportunities for Finnish field crop production, which is currently limited by the short growing season. A warmer climate will extend the thermal growing season and the physiologically effective part of it. Winters will also become milder, enabling introduction of winter-sown crops to a greater extent than is possible today. With this study we aim to characterise the likely regional differences in capacity to grow different seed producing crops. Prolongation of the Finnish growing season was estimated using a 0.5º latitude × 0.5º longitude gridded dataset from the Finnish Meteorological Institute. The dataset comprised an average estimate from 19 global climate models of the response of Finnish climate to low (B1) and high (A2) scenarios of greenhouse gas and aerosol emissions for 30-year periods centred on 2025, 2055 and 2085 (Intergovernmental Panel on Climate Change). Growing season temperature sums that suit crop growth and are agronomically feasible in Finland are anticipated to increase by some 140 °Cd by 2025, 300 °Cd by 2055 and 470 °Cd by 2085 in scenario A2, when averaged over regions, and earlier sowing is expected to take place, but not later harvests. Accordingly, the extent of cultivable areas for the commonly grown major and minor crops will increase considerably. Due to the higher base temperature requirement for maize (Zea mays L.) growth than for temperate crops, we estimate that silage maize could become a Finnish field crop for the most favourable growing regions only at the end of this century. Winters are getting milder, but it will take almost the whole century until winters such as those that are typical for southern Sweden and Denmark are experienced on a wide scale in Finland. It is possible that introduction of winter-sown crops (cereals and rapeseed) will represent major risks due to fluctuating winter conditions, and this could delay their adaptation for many decades. Such risks need to be studied in more detail to estimate timing of introduction. Prolonged physiologically effective growing seasons would increase yielding capacities of major field crops. Of the current minor crops, oilseed rape (Brassica napus L.), winter wheat (Triticum aestivum L.), triticale (X Triticosecale Wittmack), pea (Pisum sativum L.) and faba bean (Vicia faba L.) are particularly strong candidates to become major crops. Moreover, they have good potential for industrial processing and are currently being bred. Realisation of increased yield potential requires adaptation to 1) elevated daily mean temperatures that interfere with development rate of seed crops under long days, 2) relative reductions in water availability at critical phases of yield determination, 3) greater pest and disease pressure, 4) other uncertainties caused by weather extremes and 5) generally greater need for inputs such as nitrogen fertilisers for non-nitrogen fixing crops.;